Religion, dualité de l'âme et représentations du tekó porã et du tekó vai chez les peuples guarani - de Aguiar, Rodrigo Luiz Simas; Pereira, Levy Marques (Anthropologica, 2012)
This article deals with questions relating to the duality of the soul among two Guarani groups of Brazil : the Mbya and the Kayowâ. The analysis is based on classical and contemporary studies, as well as on the ethnographic data of the authors. They maintain that for these Guarani groups, con temporary daily life still largely orients itself around a vast and complex mythological corpus. It is through this corpus that one establishes an opposition between two models of personality, which serve as regulators for individual and collective actions. The Tekô Vai, a "non appropriate way of being," is thus pre sented in opposition with the Tekô Porâ, an ideal model, which determines the "good way of being," itself governed by ancestral and sacred precepts.